New frontiers in asymmetric catalysis (Wiley-Interscience, 2007)
The field of asymmetric catalysis has grown rapidly and plays a key role in drug discovery and pharmaceuticals. New Frontiers in Asymmetric Catalysis gives readers a fundamental understanding of the concepts and applications of asymmetric catalysis reactions and discusses the latest developments and findings. With contributions from preeminent scientists in their respective fields, it covers